BIM green infrastructure - exploring sustainable materials and technologies: a systematic literature review / Noor Akmal Adillah Ismail ... [et al.] - Ismail, Noor Akmal Adillah; Ramli, Hazwani; Raja Muhammad Rooshdi, Raja Rafidah; Sahamir, Shaza Rina; Marhani, Mohd Arif (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This paper presents a systematic literature review on the topic of Building Information Modelling (BIM) in the context of green infrastructure and its sustainable materials and technologies. The objective of this review is to explore the current state of knowledge regarding the application of BIM in promoting sustainable practices within the domain of green infrastructure, with a specific focus on sustainable materials and technologies. The systematic literature review follows a predefined methodology, including the identification of relevant studies, data extraction, and content analysis. Multiple academic databases were searched using appropriate keywords and criteria. The inclusion and exclusion criteria encompassed publications in peer-reviewed journals, conference proceedings, and relevant industry reports. The review reveals that BIM enables the modelling and simulation of sustainable materials to assess their environmental performance and impact. It also supports the integration of energy-efficient technologies, and smart infrastructure solutions within green infrastructure projects. However, several challenges and limitations were identified in the literature including issues related to interoperability, data standardization, and the need for improved integration between BIM and sustainability assessment tools. Limited adoption and awareness of BIM in the context of green infrastructure, along with the lack of specific guidelines and protocols, were also recognized as barriers to widespread implementation. Based on the research gaps identified in the literature, future research should focus on developing standardized frameworks and guidelines for integrating BIM with sustainable materials and technologies in green infrastructure projects. More studies are needed to assess the long-term environmental and economic benefits of BIM-enabled green infrastructure.